Treatment Outcome of Métaizeau Technique of Intramedullary Pinning in Pediatric Displaced Radial Neck Fracture - Karki, Prateek; Ranabhat, Roshani; Shah, Aman (Journal of Nepalgunj Medical College, 2020)
Introduction: Displaced radial neck fracture in children when poorly managed results in deformity of elbow and incapacitates patient’s daily activities due to compromised forearm motion, hence they require careful attention. Aims: The aim of this study is to assess the outcome of Métaizeau Technique in displaced radial neck fracture in Children. Methods: This hospital based study evaluated the treatment outcome of 35 patients with an average age of 9.34 years (range, 6 – 14 years), who presented with displaced radial neck fracture; and were treated by Métaizeau technique of intramedullary pinning by Kirschners (K) wire at Nepalgunj Medical College, Kohalpur from April 2017 to January 2020. Only Judet’s type 3 and 4 fractures were included in this study. Close reduction was attempted in all cases. All patients were followed up for an average of 8.4 months (range, 6-12 months). Functional outcome was assessed as per Métaizeau functional score. Results: All fractures united at an average of 3.77 0.84 months (meanSD). Twenty seven patients had type 3 fracture and remaining 8 had type 4a fracture. Twenty five (92.5%) patients with type 3 fracture exhibited excellent results; while three patients (37.5%) with type 4a fracture had excellent outcome. Closed reduction produced excellent outcome in all patients while 80.95% patients with percutaneous reduction had excellent result. Conclusion: Outcome depends on initial fracture type and mode of reduction. Closed reduction should be preferred over an open reduction in order to achieve superior outcome.